EFL Teachers’ Use of Digital Technology to Facilitate M-Learning - Dzul Rachman; Anis Firdatul Rochma; Paulus Widiatmoko (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Taking the concept of mobile-learning as development of instructional technology of what commonly called e-learning, this study aimed to firstly identify the digital products and approach used by EFL teachers for online instruction. Moreover, frequently used digital technologies chosen by the teachers along with contextual factors of using them were investigated. To achieve these objectives, SAMR (substitution, Adaptation, Modification, and Redefinition) model was selected as the framework of corresponding the technology use with the four levels to facilitate effective online instruction. Descriptive analysis of a questionnaire distributed to twenty-three English teachers from four universities in Indonesia resulted in almost equal distribution of technology use to facilitate m-learning purposes within the four levels. Moreover, contextual factors related to the institutional policy of online learning, the features and nature of the technology products, and the students’ varied challenges were admitted affecting teachers’ use of digital technology to facilitate m-learning.